Modélisation des connaissances et technologies du Web sémantique : deux applications au patrimoine culturel - Stefan du Château; Eunika Mercier-Laurent; Laurent Bricault; Danielle Boulanger (Humanités Numériques)
This article highlights the importance of a knowledge management approach for the digitization of cultural heritage. We present a hybrid system automatizing the cycle of information and knowledge collecting and storing for future research. This system is composed of several modules, and enables to gather information from a dictaphone according to a specified descriptive system, automatically transcribe oral information, perform linguistic analysis and information extraction, as well as semi-automatically populate a domain ontology in accordance with a predefined conceptual model. The use of an ontological extension is also presented, through an application based on an XML architecture to valorize cultural heritage in the field of Greek and Latin epigraphy.